Dynamic changes in intron retention are tightly associated with regulation of splicing factors and proliferative activity during B-cell development. Issue 3 (27th December 2019) - Ullrich, Sebastian; Guigó, Roderic
Abstract: Intron retention (IR) has been proposed to modulate the delay between transcription and translation. Here, we provide an exhaustive characterization of IR in differentiated white blood cells from both the myeloid and lymphoid lineage where we observed highest levels of IR in monocytes and B-cells, in addition to previously reported granulocytes. During B-cell differentiation, we found an increase in IR from the bone marrow precursors to cells residing in secondary lymphoid organs. B-cells that undergo affinity maturation to become antibody producing plasma cells steadily decrease retention. In general, we found an inverse relationship between global IR levels and both the proliferative state of cells, and the global levels of expression of splicing factors. IR dynamics during B-cell differentiation appear to be conserved between human and mouse, suggesting that IR plays an important biological role, evolutionary conserved, during blood cell differentiation. By correlating the expression of non-core splicing factors with global IR levels, and analyzing RNA binding protein knockdown and eCLIP data, we identify a few splicing factors likely playing an evolutionary conserved role in IR regulation. Our work provides new insights into the role of IR during hematopoiesis, and on the main factors involved in regulating IR.